Authentication and Availability in a Flexible and Adaptable Distributed File System - Neto, Mario Camara [UNESP]; Lobato, Renata Spolon [UNESP]; Manacero, Aleardo [UNESP]; Spolon, Roberta [UNESP]; Cavenaghi, Marcos Antonio; IEEE (Ieee, 2017)
A Distributed File System (DFS) is a system where the files are stored and distributed on different computers connected via a communication network. The FlexA is a DFS integrated into the user space with fault tolerance, security, scalability and flexibility features. However, FlexA has limitations in the development of new resources to the system. This work made the reengineering of the FlexA aspects such as security, database, communication, load balancing and fault tolerance. Every computer system is subject to failures, such as hardware error, communication errors and other problems that may occur. In this study, there was failure handling through monitoring of the closest machines in an overlay network, if a machine fails another takes over its work. In addition, it implemented load balancing doing the dispersion of users and data through the system, thereby obtaining a load balancing among the requests that the customer throws to the servers. Finally, incorporated a new security model with key generation using hash functions, ensuring access only to authorized people without leaving out usability.
Keywords: distributed file system; load balancing; fault recovery; security